PERTANGGUNGJAWABAN KORPORASI DALAM TINDAK PIDANA KEKERASAN SEKSUAL MENURUT UU NOMOR 12 TAHUN 2022 (Jurnal De Jure Muhammadiyah Cirebon, 2022)
The development of crime at this time is increasingly global, where there is a phenomenon that crime is not only committed by humans but also by companies or corporations. Corporate crime is not only committed in the economic sector but has penetrated into other sectors, such as sexual violence. Because the corporation is an abstract business entity, often the mechanism of corporate criminal liability is still unclear, especially in sexual violence crimes. This study aims to determine the criminal liability of corporations that commit crimes of sexual violence and know the legal consequences for corporations that commit crimes of sexual violence. This study uses normative juridical research with a statutory approach (statute approach). The results of this study are first, corporations that commit crimes of sexual violence can be subject to criminal liability regulated in Article 4 of Law Number 12 of 2022 concerning crimes of sexual violence. Second, the legal consequences for corporations that commit sexual violence crimes are regulated in Article 18 of Law Number 12 of 2022 concerning sexual violence crimes with a criminal threat of a fine of at least 5 billion, at most 15 billion.Keywords: corporate, sexual assault, crime.